Infinitely Many Coexisting Attractors in No-Equilibrium Chaotic System - Qiang Lai; Paul Didier Kamdem Kuate; Huiqin Pei; Hilaire Fotsin (Complexity)
This paper proposes a new no-equilibrium chaotic system that has the ability to yield infinitely many coexisting hidden attractors. Dynamic behaviors of the system with respect to the parameters and initial conditions are numerically studied. It shows that the system has chaotic, quasiperiodic, and periodic motions for different parameters and coexists with a large number of hidden attractors for different initial conditions. The circuit and microcontroller implementations of the system are given for illustrating its physical meaning. Also, the synchronization conditions of the system are established based on the adaptive control method.